IMPLEMENTASI MEDIA AUDIO VISUAL DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS VIII MTS WALISONGO SIMOJAYAN AMPELGADING - Muhammad Arif Nasruddin, Ayu Linda Wati (PRODI PAI FIK UNIRA MALANG, 2023)
This study aims to analyze the implementation of audio-visual media in increasing students' learning motivation in the history of Islamic culture in class VIII MTs Walisongo Simojayan Ampelgading. The educational method applied in the institution is audiovisual media. This research uses qualitative research methods. Data collection was used using interview, observation and documentation techniques. After the data is collected, data analysis is carried out by: 1) data reduction, 2) data presentation, 3) drawing conclusions. From this study, it can be seen that the audio-visual media applied at MTs Walisongo Simojayan Ampelgading can increase students' learning motivation in the history of Islamic culture in class VIII.